Study Population and Characteristic Habitat of Grizzled Leaf Monkey (Presbytis comata Desmarest, 1822) in Gunung Botol Resort, Gunung Halimun Salak National Park - Indri Septiani; Zainal Muttaqin; Dwi Agus Sasongko (Talenta Publisher, 2024)
The grizzled leaf monkey (Presbytis comata) is a protected endemic species of West Java based on the Regulation of the Minister of Environment and Forestry Number P.106/MENLHK/SETJEN/KUM.1/12/2018 concerning Protected Plant and Animal Species. The research was conducted in May-June 2022 in the Gunung Botol Resort, Gunung Halimun Salak National Park. This research aims to identify population numbers and characteristics of the grizzled leaf monkey’s habitat. This research was carried out by observation using the modified line transect method. There were 21 grizzled leaf monkey individuals consisting of 19 individuals from five groups and two solitary individuals. The distribution of meeting points is at an altitude between 1.119-1.292 masl. The population density in the three blocks ranges from 12.5 to 60 individuals/km². The estimated grizzled leaf monkey population at the Gunung Botol Resort is 785 individuals. The group size of grizzled leaf monkeys ranges from 2-6 individuals. The age structure of grizzled leaf monkeys showed a value of 42.86% for the adults and 28.57% for the pre-adult and adolescents. The results of measurements of temperature obtained an average of 19.90-21.60°C with an air humidity of 71.87-90.51%. The slope of the research block ranges from 25-40%, and the altitude ranges from 1.119-1.292 masl. The diversity of vegetation types in the Gunung Botol Resort was found in 98 species and 43 families. The tree-level vegetation type that has the highest Importance Value Index is the ki merak (Eura javanica) at 105.69%. There were 15 species of grizzled leaf monkey fodder trees identified from 11 families. There are 6 species of grizzled leaf monkey sleeping trees identified and come from 4 families